The Political Battle for Local Languages Under the Arab Domination in the Umayyad and Abbasid Caliphates - Permana, Indra Martian; Putra, Rulian Haryadi; Munandar, Asep Nur Imam (Journal La Sociale, 2025)
This study examines the political struggle for local languages under the Arab dominance during the Umayyad and Abbasid Caliphates. It explores how the expansion of Arabic influence, driven by the spread of Islam, shaped the linguistic landscape in the territories of the Islamic Empire. The research analyzes the balance between the adoption of Arabic as a language of governance, religion, and science, while also examining the persistence and development of local languages. Through a historical approach, this study highlights the efforts to preserve and promote local languages in the face of Arabization, particularly in regions such as Khorasan, Persia, and the Maghreb. The study further investigates the role of local elites, including Persian and Berber rulers, in fostering a cultural and linguistic renaissance. It concludes that while Arabic became dominant in the political and religious spheres, local languages continued to thrive, contributing to a rich linguistic and cultural diversity that shaped the Islamic world. This enduring tension between Arabic and local languages underlines the complex dynamics of language, power, and identity during the early Islamic period.